Laser Beam Melting of Metals - Nahr, Florian; Schmidt, Michael (Progress in Powder Based Additive Manufacturing, 2025)
In the powder bed fusion of metals applying a laser beam (PBF-LB/M), components are built layer-wise by melting a thin bed of powder using a laser beam as an energy source. The build chamber is filled with shielding gas using purified Argon or Nitrogen to prevent oxidation and allow for efficient heat conduction and convective cooling of the build surface. Although laser beam melting operates at ambient temperatures, most of the PBF-LB/M machines are capable of substrate preheating. The powder particles absorb the photons in the first microseconds after the impact of the laser beam and generate a melt pool. The photons are subsequently further absorbed by the melt pool as the latter moves ahead, melting the powder layer to form the desired geometry [13]. It supports a wide variety of metals, ranging from steels over titanium alloys to nickel-based super alloys, just to name a few. Since PBF-LB/M shows great potential for functionally optimized and lightweight designs, the processing of aluminum alloys is of particular interest [9